Law and the urban poor in India - Iyer, Krishna V.R. (Delhi, 1988)
This book is a masterly survey of the problem of the urban poor in India and how the same be successfully tackled. The writer has given a graphic account the lives of pavement can of dwellers in India and their sufferings. He has discussed the important cases decided by the Supreme Court of India dealing with this problem and pointed out how those judge ments have failed to meet the requirements of the situation. He has emphasized the gravity of the situation and the necessity for quick action if a calamity is to be avoided in the future. While reading the book one wonders at the encyclopaedic knowledge of the writer who really feels for the suffering urban poor and would like to carry on a crusade on their behalf.
Keywords: Law India